Principles of Soft Computing Using Python Programming : Learn How to Deploy Soft Computing Models in Real World Applications - Nandi, Gypsy (John Wiley & Sons, Inc., 2024)
"Soft computing is an innovative approach to computing which parallels the remarkable ability of the human mind to reason and learn in an environment of uncertainty and imprecision. Soft computing techniques have the roots in machine learning, fuzzy logic, evolutionary computation, and probabilistic theory. Hence, it is a vital tool used for performing several computing operations. Often it has been noticed that no fixed solution can be found for a computationally hard task. In such a case, a precisely stated analytical model may not work to produce precise results. For this, the soft computing approach can be used that does not require a fixed mathematical modelling for problem solving. In fact, the uniqueness and strength of soft computing lie in its superpower of fusing of two or more soft computing computational models/techniques to generate optimum results"--